Perspectives on community-based system change for people living with persistent pain: insights from developing the “Rethinking Pain service” - Johnson, Mark I.; Page, Kerry; Woodall, James; Thompson, Kate (Frontiers in Pain Research, 2024)
In this perspective article we advocate community-based system change for people living with persistent pain. Our view is that greater use of the voluntary and community sector, in partnership with the clinical sector, creates the conditions for a “whole person” approach to pain management, leading to greater personalised care for adults living with long-term pain whilst having the potential to ease some of the pressures on General Practitioners and other clinical services. We advocate pain care that is socially connected, meaningful within socio-cultural contexts and aligned with the principles of salutogenesis. We provide an example of a UK National Health Service (NHS) commissioned pain service called “Rethinking Pain” that operationalises this perspective. Led by the voluntary and community sector, Rethinking Pain works in partnership with the clinical sector to provide a central holistic pathway of care for people experiencing persistent pain. This is the first time that this model of care has been commissioned for persistent pain in this area of England. The Rethinking Pain service is underpinned by core values to work with people to manage their pain holistically. The Rethinking Pain team proactively engage with people in the community, actively approaching and engaging those who experience the biggest health inequalities. In this article we provide an overview of the context of pain services in the UK, the rationale and supporting evidence for community-based system change, and the context, pathway, values, goals, and aspirations of the Rethinking Pain service.